Utilization Of Cogon Grass Waste As Biofoam For Styrofoam Substitute - Maharani, Alenta Ayudia; Maheswari, Aliyah Srihayu; Rasyida, Athifa Aptriasa; Batrisya, Azzita Afiqah; Angelita, Cantika Mutiara; Rahman, Izzati Aulia (Kolej PERMATA Insan, 2025)
Insan Junior Researcher International Conference & Innovation (iJURECON) 2025 : “STREAM for a Better Future/ editor : Ahmad Fuad Mohamad Amin, Nurul Shazwani Binti Mohamed, Rossidi Bin Usop, Abdel Rahman Ibrahim Suleiman Islieh Organised by Kolej PERMATA Insan 10-11 October 2025